Analisis Belanja Modal Pemerintah Daerah Kabupaten Kepulauan Talaud - Gaghauna, Richard D E; Saerang, David P E; Warongan, Jessy (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2017)
Abstract. This research is aimed to understand the obstacles of disbursing capital expenditures in Talaud local government and strategies to overcome such problems. This is an exploratory qualitative research. The sampling method is purposive sampling. Data were collected by in-depth interviews and documentation studies. This study concludes that there are several obstacles in the capital expenditures obstacles within: (a) the stage of budget planning, (b) capital expenditure disbursement and (c) in the responsibility stage. The main factors causing those obstacles are the low quality of the human resources, lack of knowledges in performing their tasks and functions as the officers and providers to supplies, budget limitation, and lack of commitment of the district head, insufficient of continuous and periodic supervision. There are 4 types of strategy implemented to overcome the obstacles in relation to SWOT: Â (1) SO (strengths-opportunities) strategies are used to overcome the low quality of the human resources and commitment of the district head, (2) WO (weaknesses-opportunities) strategies are employed to overcome budget limitation, (3) ST (strength-threats) strategies are conducted to resolve continuous and periodic supervision and evaluation for improvement, (4) WT (weakness-threats) strategies are implemented to solve insufficient Â knowledge knowledges in performing their tasks and functions as the officers and providers to supplies.Keywords: Capital expenditure, Planning, Capital expenditure execution, monitoring.Abstrak. Penelitian ini bertujuan untuk mengetahui kendala atau penghambat pelaksanaan belanja modal Pemerintah Kabupaten Kepulauan Talaud dan bagaimana strategi mengatasinya. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan eksploratif (exploratory approach). Teknik sampling penelitian ini adalah purposive sampling. Sedangkan teknik pengumpulan data adalah dengan wawancara, dan studi dokumentasi. Disimpulkan bahwa kendala dibagi menjadi (a) kendala Perencanaan anggaran, (b) pelaksanaan belanja modal dan (c) pertanggungjawaban. Faktor-faktor utama pendukung kendala adalah kendala rendahnya kualitas SDM, kendala kurangnya pemahaman terhadap tugas pokok dan fungsi pejabat pelaksana kegiatan dan penyedia barang/jasa, kendala ketersediaan anggaran dan kendala komitmen pimpinan daerah, kendala pengawasan dan evaluasi secara berkala dan terus menerus. Strategi yang diformulasikan adalah dengan mengunakan matrix SWOT, ditemukan 4 jenis strategi: (1) Strategi SO (strengths-opportunities) untuk mengatasi kendala penghambat rendahnya kualitas SDM dan komitmen pimpinan daerah, (2) Strategi WO (weaknesses-opportunities) digunakan untuk Untuk mengatasi kendala ketersediaan anggaran kendala, (3) Strategi Strategi ST (strength-threats) untuk mengatasi kendala pengawasan dan evaluasi secara berkala dan terus menerus, (4) Strategi WT (weakness-threats) untuk mengatasi kendala penghambat kurangnya pemahaman terhadap tugas pokok dan fungsi pejabat pelaksana kegiatan dan penyedia barang/jasa.Kata Kunci: Belanja modal, Perencanaan, Pelaksanaan belanja modal, Pengawasan.